Sistem Pengelolaan Logistik Obat di Puskesmas Makkasau Kota Makassar - Lusyana Aripa; Kristina Jeliman; Nur Hamdani Nur (Journal of Health Quality Development, 2022)
Drug management is one of the pharmacy service activities which includes planning, requesting, receiving, storing, distributing, destroying or with drawing, using, recording, and reporting. Objectives: this study aimed to find out the drug logistics management system in usage planning, requesting, receiving, storing, distributing, using, recording, and reporting at Makkasau Health Center, Makassar in 2020. This study was qualitative research with a phenomenological appr each. The informants were selected by using the purposive sampling technique in which the gained total of informants was five people. Data were collected through an in-depth interview and direct observation at Makkasau Health Center, Makassar in 2020. The results showed that the drug planning at Makkasau Health Center has been in line with the drug management guidelines. Drug requests at Makkasau Health Center have also been carried out according to available procedures. This can be seen in the implementation of drug requests on the health office through LPLPO to regency/city pharmacy warehouses (in Indonesian: Gudang Farmasi Kabupaten/Kota (GFK)) based on the guidelines for drug management. The drug acceptance at Makkasau Health Center has been carried out as well according to the procedure. Drug storage at Makkasau Health Center has not been categorized in the good drug storage standards. This is because the available medicine warehouse has minimal space and does not have enough shelves. The drug distribution at Makkasau Health Center has not been according to the procedure. This can be seen from the distribution of medicines from district/city pharmacy warehouses that is not based on the guidelines for drug management. Drug use at Makkasau Health Center has been according to the standard procedures. This can be seen by the implementation of rational drug prescribing based on the drug management guidelines. Drug recording and reporting at Makkasau Health Center have been according to the procedure. This can be seen by the implementation of daily recording and monthly reporting using the Drug Usage Report and Request Sheet (in Indonesian: Laporan Pemakaian dan Lembar Permintaan Obat (LPLPO)